Desarrollo, estandarización y aplicación de herramientas de tipificación molecular de poblaciones de Trypanosoma cruzi en muestras clínicas, vectores y reservorios de la enfermedad de Chagas - Cura, Carolina Inés (2014)
Natural populations of Trypanosoma cruzi, the causative agent of Chagas disease, are composed of multiple clones, classified into 6 discrete typing units (DTUs TcI-TcVI), with different distribution in geographical regions and transmission cycles. In certain areas of South America, T. cruzi and Trypanosoma rangeli (related trypanosome specie) infections frequently overlap, and differential diagnosis by conventional techniques is often complicated. In this work, new real time PCR algorithms for the identification of the six T. cruzi DTUs, and the differential detection of T. cruzi and T. rangeli, directly in biological samples using TaqMan probes, have been developed and validated. These methods, which involve one or two sequential PCR reactions, depending on the DTU being analyzed, showed a high specificity and an analytical sensitivity comparable with conventional typing methods used in our laboratory. The new methods were used for the characterization of strains and samples derived from different eco-epidemiological and clinical scenarios. Furthermore, we have studied the genetic diversity within TcI and TcIII using the intergenic sequence of the miniexón gene.\n